(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
"Language Awareness for Learners" explores the importance of understanding language beyond its basic structures and rules. It emphasizes the significance of recognizing language in its social, cultural, and communicative contexts. The article highlights how developing language awareness enhances communication skills, promotes cultural understanding, and fosters appreciation for linguistic diversity. Practical strategies for learners to cultivate language awareness, such as immersion in authentic language materials and engagement in language exchange programs, are provided. Additionally, the article encourages embracing linguistic diversity and overcoming challenges in language learning through perseverance and support. Ultimately, it underscores the transformative power of language awareness in shaping learners’ linguistic proficiency and global perspective.